Ektacytometry Analysis of Post-splenectomy Red Blood Cell Properties Identifies Cell Membrane Stability Test as a Novel Biomarker of Membrane Health in Hereditary Spherocytosis - Berrevoets, M. C.; Bos, J.; Huisjes, R.; Merkx, T. H.; van Oirschot, B. A.; van Solinge, W. W.; Verweij, J. W.; Lindeboom, M. Y. A.; van Beers, E. J.; Bartels, M.; van Wijk, R.; Rab, M. A. E. (Frontiers in Physiology, 2021)
Hereditary spherocytosis (HS) is the most common form of hereditary chronic hemolytic anemia. It is caused by mutations in red blood cell (RBC) membrane and cytoskeletal proteins, which compromise membrane integrity, leading to vesiculation. Eventually, this leads to entrapment of poorly deformable spherocytes in the spleen. Splenectomy is a procedure often performed in HS. The clinical benefit results from removing the primary site of destruction, thereby improving RBC survival. But whether changes in RBC properties contribute to the clinical benefit of splenectomy is unknown. In this study we used ektacytometry to investigate the longitudinal effects of splenectomy on RBC properties in five well-characterized HS patients at four different time points and in a case-control cohort of 26 HS patients. Osmotic gradient ektacytometry showed that splenectomy resulted in improved intracellular viscosity (hydration state) whereas total surface area and surface-to-volume ratio remained essentially unchanged. The cell membrane stability test (CMST), which assesses the in vitro response to shear stress, showed that after splenectomy, HS RBCs had partly regained the ability to shed membrane, a property of healthy RBCs, which was confirmed in the case-control cohort. In particular the CMST holds promise as a novel biomarker in HS that reflects RBC membrane health and may be used to asses treatment response in HS.